Electrocatalytic, Kinetic, and Mechanism Insights into the Oxygen‐Reduction Catalyzed Based on the Biomass‐Derived FeOx@N‐Doped Porous Carbon Composites. Issue 19 (30th March 2021) - Lu, Zhiwei; Chen, Jinpeng; Wang, WenLi; Li, Wenjin; Sun, Mengmeng; Wang, Yanying; Wang, Xianxiang; Ye, Jianshan; Rao, Hanbing
Abstract: A valid strategy for amplifying the oxygen reduction reaction (ORR) efficiency of non‐noble electrocatalyst in both alkaline and acid electrolytes by decorated with a layer of biomass derivative nitrogen‐doped carbon (NPC) is proposed. Herein, a top‐down strategy for the generally fabricating NPC matrix decorated with trace of metal oxides nanoparticles (FeO x NPs) by a dual‐template assisted high‐temperature pyrolysis process is reported. A high‐activity FeO x / FeNC (namely Hemin/NPC‐900) ORR electrocatalyst is prepared via simply carbonizing the admixture of Mg5 (OH)2 (CO3 )4 and NaCl as dual‐templates, melamine and acorn shells as nitrogen and carbon source, hemin as a natural iron and nitrogen source, respectively. Owing to its unique 3D porous construction, large BET areas (819.1 m 2 ∙g −1 ), and evenly dispersed active sites (FeN x, CN, and FeO parts), the optimized Hemin/NPC‐900 catalyst displays comparable ORR catalytic activities, remarkable survivability to methanol, and preferable long‐term stability in both alkali and acid electrolyte compared with benchmark Pt/C. More importantly, density function theory computations certify that the interaction between Fe3 O4 nanoparticles and arm‐GN (graphitic N at armchair edge) active sites can effectually promote ORR electrocatalytic performance by a lower overpotential of 0.81 eV. Accordingly, the research provides some insight into design of low‐cost non‐precious metal ORR catalysts in theory and practice. Abstract : Newly designed iron‐nitrogen‐co‐doped porous carbon material decorated with FeO x nanoparticles derived from biomass, which have large specific surface area, high degree of graphitization, and abundant atomically dispersed Fe‐N x active sites, enhanced mass transport and O2 diffusion. Superior oxygen reduction reaction performance in both acidic and alkaline solution based on experiment and density function theory calculation was obtained.